Corporate Governance and Its Role in Shaping Environmental Disclosure with Environmental Performance as a Moderating Factor - Sulistiyani; Nur Rahman, Arif (Advances in Environmental Innovation, 2024)
Objective: This study aims to investigate how corporate governance influences environmental disclosure practices among Indonesian firms and to examine the moderating effect of environmental performance on this relationship.Methods: A quantitative correlational design was employed, utilizing data from 27 companies listed on the Indonesia Stock Exchange (IDX) that participated in the PROPER assessment from 2018 to 2023. Regression analysis was conducted to explore the relationships and interactions among these variables.Results: Analysis demonstrated a notable positive relationship between corporate governance and environmental disclosure, indicating that stronger governance practices are associated with higher levels of environmental reporting. Additionally, environmental performance was found to moderate this relationship, enhancing the effect of corporate governance on disclosure when performance is robust. The study also revealed differences across sectors, with industries such as Consumer Goods and Banking exhibiting the highest levels of governance, performance, and disclosure.Novelty: This study offers a novel perspective by integrating environmental performance as a moderating factor in the relationship between corporate governance and environmental disclosure. While previous research has primarily focused on the direct effects of governance on disclosure, this study extends the understanding by highlighting how environmental performance influences this relationship. It provides a comprehensive view of how both governance and performance interplay to shape corporate transparency in environmental reporting.Implication: The findings underscore the critical role of corporate governance and environmental performance in shaping environmental disclosure. By aligning with stakeholder theory, firms are encouraged to enhance governance and performance for greater transparency.